2015
DOI: 10.1532/hsf.1256
|View full text |Cite
|
Sign up to set email alerts
|

Ankaferd Blood Stopper Decreases Postoperative Bleeding and Number of Transfusions in Patients Treated with Clopidogrel: A Double-blind, Placebo-controlled, Randomized Clinical Trial

Abstract: The use of local ABS reduces bleeding, transfusion requirements of packed red blood cells, platelets and total blood units in patients premedicated with clopidogrel and ASA undergoing emergent CABG .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The antithrombin activity of ABS is important especially in cardiac surgery. ABS was shown not to have the risk of thrombin-induced thrombotic complications by cardiac surgeons during open heart surgery (14)(15)(16)(17). The demonstration of the antierythroid aggregation of ABS is an important result in terms of the antihemorrhagic effect that does not create a risk of thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…The antithrombin activity of ABS is important especially in cardiac surgery. ABS was shown not to have the risk of thrombin-induced thrombotic complications by cardiac surgeons during open heart surgery (14)(15)(16)(17). The demonstration of the antierythroid aggregation of ABS is an important result in terms of the antihemorrhagic effect that does not create a risk of thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…There are two studies regarding this issue. In both studies 25 patients were included and ABS is shown to reduce bleedings significantly (Atalay et al 2015; Akpinar et al 2015). Apart from these clinical efficiency data, unfortunately in the literature there are limited data regarding safety in tissue level.…”
Section: Discussionmentioning
confidence: 99%
“…ABS is shown to be effective and safely used in the emergent beating heart coronary artery bypass grafting (Atalay et al 2015). Moreover, ABS could control the hemorrhages in the cases who were using antiagregant treatment and undergone emergency bypass operation (Akpinar et al 2015). Besides those valuable data for the efficacy of ABS, there is no available data regarding the ultrastructural analysis of ABS at tissue level.…”
Section: Introductionmentioning
confidence: 99%
“…Ankaferd is the first Turkish medical product officially accredited by the Turkish Ministry of Health. Recently, ABS has been shown to produce local hemostasis by acting topically after major arterial vessel injury . Reducing the compression time during patent hemostasis by facilitating hemostasis may decrease RAO.…”
Section: Introductionmentioning
confidence: 99%